Charitable behavior: Christian beliefs that explain donor intentions - Poplaski, Stephen C. (Kansas State University, 2017)
The purpose of this research study was to investigate the determinants that explain and predict Christian’s intentions to make lifetime gifts to charities. The research was guided by the theory of planned behavior (Ajzen, 1991) utilizing an expanded model that anticipated Christians who have (a) a favorable attitude toward giving, (b) a perceived pressure from social norms, (c) high levels of perceived behavioral control in their ability to make gifts, (d) a positive moral responsibility toward charitable giving, (e) a history of charitable giving, and (f) a faith based spiritual desire to pursue the Christian way of life would be more inclined to have giving intentions. Survey data were obtained through two pilot studies and a main study (N = 250). The pilot study participants were recruited through the researcher’s social network. The main study participants were enlisted through a contract with Qualtrics, an online survey organization that maintains panels of likely research subjects. Hierarchical linear regression identified support for traditional and expanded models of the theory of planned behavior. In the traditional model, attitude, subjective norm, and perceived behavioral control, all predicted donative intent. In the expanded model, not moral norms, past behavior, and the Christian way of life predicted donating intentions; however, perceived behavioral control a significant predictor in the traditional model, did not predict donative intent. The traditional theory of planned behavior accounted for 65%, and expanded predictors added 11% to the explanation of intention to donate to non-profit organizations in the coming year. The current research has both theoretical and applied implications. Consistent with Fishbein and Ajzen’s (2010) encouragement to improve the traditional model, the expanded model enhanced the predictive ability of the theory of planned behavior with a new determinant, the Christian way of life. The current research also reaffirms the predictive ability of the previously tested factor past behavior and not moral norms. Non-profit organizations may apply these findings by targeting the salient beliefs that are foundational to all predictors of intentions. The current research has identified beliefs associated with attitudes, social norms, perceived behavioral control, moral norms, past behavior, and the Christian way of life that offer non-profit organizations educational opportunities to intervene with donors to improve charitable behavior.
Keywords: charitable giving; spirituality; donations; Christian beliefs; charitable behaviorChristian giving